China's allocation of fixed capital investment, 1952-1957 - Zheng, Zhuyuan (Michigan papers in Chinese studies ;, 1974)
China's efforts to stimulate industrial development and economic growth through the allocation of investments are analyzed. Cheng concludes with an overall assessment of the distinctive features of the allocation pattern. Includes 41 statistical tables.